A Remark on the Courant-Friedrichs-Lewy Condition in Finite Difference Approach to PDE's (Advances in Applied Mathematics and Mechanics, 2014)
The Courant-Friedrichs-Lewy condition (The CFL condition) isappeared in the analysis of the finite difference methodapplied to linear hyperbolic partial differential equations.We give a remark on the CFL condition from a view point ofstability, and we give some numerical experimentswhich show instability of numerical solutions even under theCFL condition. We give a mathematical model for rounding errorsin order to explain the instability.